MITOS PADA MEME REFERENSI BUDAYA POPULER DALAM KNOWYOURMEME.COM (ANALISIS SEMIOTIK) - Sally, Seyla; Rambing, Rosalina; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â Â Â Â Meme is a humorous picture that is used as a way of communicating ideas. Nowadays meme is does not only function as a fun way to communicate but also as a campaign medium, as advertisements, etcetera. That is why the writer decided to do a research entitled â€œMyth on Popular Culture Reference Meme on Knowyourmeme.comâ€. As a requirement to achieve the Bachelor Degree in English Department at Faculty of Humanities in Sam Ratulangi, this skripsi entitled â€œMyth on Popular Culture Reference Meme on Knowyourmeme.comâ€ is finished and submitted. This research aims to identify and classify the signifier and signified element of pop culture reference memes. The result of the previous step will be used to analyze the myth in each meme to find out the new concept or new meaning. The writer used qualitative research method in this research. The data were collected from knowyourmeme.com and were analyzed using Barthesâ€™ theory of myth. The new concept of each meme is dependent on the objective of the maker and could change according to the composition of text and image in the meme. This research is expected to be able to help students and readers in learning semiotics and the making of another researches about memes and semiotics.Keywords: Semiotic, Myth, Meme, Pop Culture Reference